Lord of vice ebook - Ridley, Erica (Rogues to Riches., 2018)
Appearances can be deceiving... Vice merchant Maxwell Gideon is wickedly handsome, sinfully arrogant, and devilishly ruthless. Rumor has it, his gaming hell has the power to steal souls and grant miracles. Truth is, Max only owns half of The Cloven Hoof. He'd buy out his silent partner if he knew the man's identity. But it's hard to focus on business matters when a fallen angel tumbles right into one's lap... Miss Bryony Grenville has a well-earned reputation as an unrepentant hoyden. But even the gossipiest of the pinch-faced matrons ruling High Society could never imagine the daughter of a baron secretly financing the ton's most infamous gambling parlor. Its maddening, sexy proprietor doesn't suspect a thing... and two can play at temptation! In the Rogues to Riches historical romance series by USA Today and New York Times bestselling author Erica Ridley, Cinderella stories aren't just for princesses...